A Dual‐Phase Ceramic Membrane with Extremely High H2 Permeation Flux Prepared by Autoseparation of a Ceramic Precursor. Issue 36 (27th July 2016) - Cheng, Shunfan; Wang, Yanjie; Zhuang, Libin; Xue, Jian; Wei, Yanying; Feldhoff, Armin; Caro, Jürgen; Wang, Haihui
Abstract: A novel concept for the preparation of multiphase composite ceramics based on demixing of a single ceramic precursor has been developed and used for the synthesis of a dual‐phase H2 ‐permeable ceramic membrane. The precursor BaCe0.5 Fe0.5 O3− δ decomposes on calcination at 1370 °C for 10 h into two thermodynamically stable oxides with perovskite structures: the cerium‐rich oxide BaCe0.85 Fe0.15 O3− δ (BCF8515) and the iron‐rich oxide BaCe0.15 Fe0.85 O3− δ (BCF1585), 50 mol % each. In the resulting dual‐phase material, the orthorhombic perovskite BCF8515 acts as the main proton conductor and the cubic perovskite BCF1585 as the main electron conductor. The dual‐phase membrane shows an extremely high H2 permeation flux of 0.76 mL min −1  cm −2 at 950 °C with 1.0 mm thickness. This auto‐demixing concept should be applicable to the synthesis of other ionic‐electronic conducting ceramics. Abstract : A dual‐phase ceramic membrane consisting of 50 mol % BaCe0.85 Fe0.15 O3− δ and 50 mol % BaCe0.15 Fe0.85 O3− δ is formed automatically by demixing of BaCe0.5 Fe0.5 O3− δ through calcination. The first perovskite phase acts as the main proton conductor and the other as the main electron conductor. The composite ceramic shows an extremely high H2 permeation flux. This concept can also be used for the synthesis of other ceramics.